(untitled) (Ocean and Coastal Research, 2022)
This study is focused on the fate of a large volume of mine slurry discharged from the Doce River (DR) to the coastal ocean after the worst environmental disaster in Brazilian which occurred in November 2015. We used Eulerian (ROMS) and Lagrangian (STRiPE) numerical models, as well as satellite remote sensing data, to study the spreading and seafloor accumulation of fine river-borne sediments during the initial six months following the disaster. We show that the regions of intense sediment accumulation were determined by spreading patterns of the surface-advected DR plume. The river discharge rate governed the plume surface area, while its position depended on local wind forcing conditions. The spreading of sediments carried by the DR plume was dominated by southward transport caused by prevailing upwelling-favorable northeasterly winds during the study period. Under high discharge conditions, river-borne sediments were transported over 100 km southward from the DR mouth and reached the outer shelf. In contrast, sediments were arrested near the mouth during drought periods and remained on the inner shelf. As a result, fine river-borne sediments accumulated on the seafloor, mainly in the large shallow shelf area southward from the DR mouth. Conversely, only a small fraction of residue was deposited northward. Thus, the Environmental Protection Area (EPA) of Costa das Algas, located 40 km southward from the DR, potentially exhibited more susceptibility to sediment arrival. On the other hand, their influence on Abrolhos Marine National Park, located 200 km northeastward from the DR mouth, was presumably minimal.